The Trump presidency : continuity and change in US foreign policy - Hill, Matthew Alan Herausgeber; Hurst, Steven, 1968- 1968- Herausgeber (Routledge, Taylor & Francis Group, 2023)
"Did Donald Trump decisively transform and alter the course of US foreign policy? All presidents promise change, but few presidents promise changes as radical as Trump did during his presidency. The extent to which Trump delivered on that promise, however, remains hotly debated with little or no agreement. The chapters in this edited volume argue that much of this debate is a dialogue of the deaf where scholars speak past rather than to each other, where the basis for claims about change or continuity is unclear and where the argument and knowledge, consequently, fails to progress. At its heart, this is a problem of theory and methods. Employing a diverse range of theoretical and methodological perspectives, this book seeks to move the debate beyond a superficial focus on events to more fundamental questions of how change is defined, measured and explained and in doing so, attempts to advance understanding of foreign policy change and the extent to which Trump can really be considered to have been a transformative president."